2018
DOI: 10.1007/s10147-017-1225-8
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the prognosis between adenocarcinoma and squamous cell carcinoma in stage IB–IIA cervical cancer

Abstract: In stage IB-IIA CC, there is no difference in prognosis between AC and SCC. The ovaries of stage IB-IIA1 AC patients under age 45 might be preserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 33 publications
1
36
0
Order By: Relevance
“…Controversy persists regarding differences in survival outcomes between ADC and SCC in patients with cervical cancer [ 6 8 9 10 11 12 ]. In the present study, we performed a PSM analysis to compare survival outcomes between patients with cervical ADC and SCC from the SEER database.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Controversy persists regarding differences in survival outcomes between ADC and SCC in patients with cervical cancer [ 6 8 9 10 11 12 ]. In the present study, we performed a PSM analysis to compare survival outcomes between patients with cervical ADC and SCC from the SEER database.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the International Federation of Gynecology and Obstetrics (FIGO) staging system is the most accurate classification used to predict the prognosis and guide the treatment of cervical cancer. However, no difference in treatment strategies has been identified between SCC and ADC [ 8 ]. Many studies have attempted to determine whether these different histological subtypes have any effect on survival.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of ovarian metastases was 0% in stage IA, 2.8% in stage IB, 3.4% in stage IIA, and 11.8% in stage IIB cervical adenocarcinoma. Five studies (7, 9, 12, 22, 26) showed that FIGO stage, tumor size, DSI, LNM, and vaginal invasion are significantly related to poor prognosis. Nine studies (7, 14, 16, 17, 2934) reported that age, FIGO stage, tumor size, DSI, parametrial invasion (PMI), corpus uteri invasion (CUI), LNM, vaginal invasion, and blood vessel invasion are significantly associated with ovarian metastases.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, the studies on the relationship of keratinized cervical squamous cell carcinoma and patient prognosis has been controversial. It’s been reported [ 37 39 ] that compared with non-keratinized cervical squamous cell carcinoma, the survival rate of keratinized cervical squamous cell carcinoma is significantly reduced, and it is not sensitive to radiotherapy, and the prognosis is very poor for untreated patients or advanced patients. Therefore, differentiate the various subtypes of squamous cell carcinoma of cervix is very helpful in clinical management.…”
Section: Discussionmentioning
confidence: 99%